MEMBINCANG KONSEP TAWARRUQ DALAM DUNIA PERBANKAN DEWASA INI - Samsuri, Ali (UNIVERSUM, 2015)
Tawarruq contract is that if someone buys goods from a seller to credit the price and he sells the goods in cash to a third party other than the seller at a cheaper price. The goal is to get the cash. Tawarruq transaction models is used as a form of transaction in the banking system. The existence of this Tawarruq contract can help Islamic banks in the world were very limited and very limited business anyway. The use of contract Tawarruq can help improve the liquidity of Sharia banking, but set the MUI fatwa banning the use of Tawarruq contract in Indonesia. Whereas in some other countries that have Sharia banking system, this agreement is allowed to use it. One of these neighboring Indonesia itself, namely Malaysia. Article outlines a comparative analysis on the MUI fatwa expression in the four main schools of jurisprudence. School of Imam Opinions are divided into two groups; The first group may judge, while the next group judge illegitimate. With maslahah theory, the MUI fatwa needs to be reviewed in view of the importance of the contract Tawarruq to improve the competitiveness of Sharia banking.Keywords;  Tawarruq, ba'i al-'inah, hilah, Perbankan Syari’ah